The anatomy of violence: the biological roots of crime - Raine, Adrian (Pantheon Books, 2013)
"Provocative and timely: a pioneering neurocriminologist introduces the latest biological research into the causes of--and potential cures for--criminal behavior. A leading criminologist who specializes in the neuroscience behind criminal behavior, Adrian Raine introduces a wide range of new scientific research into the origins and nature of violence and criminal behavior. He explains how impairments to areas of the brain that control our ability to experience fear, make decisions, and feel empathy can make us more likely to engage in criminal behavior. He applies this new understanding of the criminal mind to some of the most well-known criminals in history. And he clearly delineates the pressing considerations this research demands: What are its implications for our criminal justice system? Should we condemn and punish individuals who have little to no control over their behavior? Should we act preemptively with people who exhibit strong biological predispositions to becoming dangerous criminals? These are among the thorny issues we can no longer ignore as our understanding of criminal behavior grows"--